Design of Tailor-Made Biopolymer-Based Capsules for Biological Application by Combining Porous Particles and Polysaccharide Assembly - Cléa Chesneau; Laura Larue; Sabrina Belbekhouche (MDPI AG, 2023)
Various approaches have been described in the literature to demonstrate the possibility of designing biopolymer particles with well-defined characteristics, such as size, chemical composition or mechanical properties. From a biological point of view, the properties of particle have been related to their biodistribution and bioavailability. Among the reported core-shell nanoparticles, biopolymer-based capsules can be used as a versatile platform for drug delivery purposes. Among the known biopolymers, the present review focuses on polysaccharide-based capsules. We only report on biopolyelectrolyte capsules fabricated by combining porous particles as a template and using the layer-by-layer technique. The review focuses on the major steps of the capsule design, i.e., the fabrication and subsequent use of the sacrificial porous template, multilayer coating with polysaccharides, the removal of the porous template to obtain the capsules, capsule characterisation and the application of capsules in the biomedical field. In the last part, selected examples are presented to evidence the major benefits of using polysaccharide-based capsules for biological purposes.